2020
DOI: 10.3389/fcell.2020.00032
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginyl-tRNA Synthetase, a Novel Component of Hippo Signaling, Binds to Salvador and Enhances Yorkie-Mediated Tumorigenesis

Abstract: Aminoacyl-tRNA synthetases (ARSs), which are essential for protein translation, were recently shown to have non-translational functions in various pathological conditions including cancer. However, the molecular mechanism underlying the role of ARSs in cancer remains unknown. Here, we demonstrate that asparaginyl-tRNA synthetase (NRS) regulates Yorkie-mediated tumorigenesis by binding to the Hippo pathway component Salvador. NRS-RNAi and the NRS inhibitor tirandamycin B (TirB) suppressed Yorkie-mediated tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Zhong et al (2015) observed that IARS2 was highly expressed in human colon cancer tissues, and knockdown of IARS2 could inhibit RKO cell proliferation, suggesting that IARS2 might trigger the development of colon cancer. Furthermore, NRS induced Yorkie-mediated tumor phenotypes in a Drosophila model ( Yeom et al, 2020 ). During this process, NRS blocked the interaction between Salvador and Hippo by binding to Salvador, thereby activating Yorkie target genes via decreasing Yorkie phosphorylation ( Yeom et al, 2020 ).…”
Section: Roles Of Arss In Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…Zhong et al (2015) observed that IARS2 was highly expressed in human colon cancer tissues, and knockdown of IARS2 could inhibit RKO cell proliferation, suggesting that IARS2 might trigger the development of colon cancer. Furthermore, NRS induced Yorkie-mediated tumor phenotypes in a Drosophila model ( Yeom et al, 2020 ). During this process, NRS blocked the interaction between Salvador and Hippo by binding to Salvador, thereby activating Yorkie target genes via decreasing Yorkie phosphorylation ( Yeom et al, 2020 ).…”
Section: Roles Of Arss In Cancermentioning
confidence: 99%
“…Furthermore, NRS induced Yorkie-mediated tumor phenotypes in a Drosophila model ( Yeom et al, 2020 ). During this process, NRS blocked the interaction between Salvador and Hippo by binding to Salvador, thereby activating Yorkie target genes via decreasing Yorkie phosphorylation ( Yeom et al, 2020 ). Notably, YAP, a mammalian homolog of Yorkie, target genes were upregulated in colon cancer C26 cells, and NRS inhibitor TirB decreased the levels of YAP target genes and suppressed cell proliferation in C26 cells, indicating that NRS might regulate the development of colon cancer by Hippo signaling pathway ( Yeom et al, 2020 ).…”
Section: Roles Of Arss In Cancermentioning
confidence: 99%
See 3 more Smart Citations